Chicago Paper - Experimental Investigations on the " Loss of Head" of Air-Currents in Underground Working - D. Murgue (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1894)
The circulation of air in underground workings is subject to a gradual and continuous reduction of its pressure, from intake to outlet, caused by the friction between it and the more or less rough and uneven surfaces of the passages. For comparison with the flow